Chironomids are commensals of the larvae and pupae of Blephariceridae and Simuliidae from the North Caucasus (Diptera: Chironomidae: Orthocladiinae) - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2022)
Illustrated morphological descriptions of chironomid larvae from subfamily Orthocladiinae Cardiocladius sp. 1, which as commensals live between ventral suckers of Blephariceridae larvae, as well as larvae and pupae of Eukiefferiella claripennis group inhabited of Simuliidae pupal cocoons, are given. DNA barcodes of these chironomid species and sequences of their hosts, three species of Liponeura Loew (Blephariceridae) and one species of Simulium aff. variegatum (Simuliidae), are provided.